MEMAHAMI MEKANISME PASAR DALAM KONTEKS ISLAM - Firmansyah, Andre; Andri Purnawan; Udin Saripudin (PT Wahana Global Education, 2025)
This article aims to explain the nature of market mechanisms in Islamic economic thought and their current practice. A historical and philosophical approach is used in the analysis to examine the basic teachings of Islam on markets and to explore the ideas and insights of Islamic scholars on this subject. The article concludes that within the Islamic framework, market mechanisms have been considered a vital part of economic activity, such that their existence has been a primary concern of Islamic scholars. Market mechanisms that protect society with fair and just prices are also considered essential and necessary for a better life. This, in turn, implies the need to maintain market mechanisms, where market equilibrium occurs at the intersection of the supply and demand curves in a state of mutual consent. If anything disturbs this equilibrium, the government must intervene in the market.